Personality Analysis of the Main Character in the Film Ngeri-Ngeri Sedap by Bene Dion, a Study of Literary Psychology - Misbah, Misbah; Lubis, Lailan Syafira Putri; Ray, Sukma Adelina (Lembaga Riset Mutiara Akbar, 2025)
This study aims to describe the personality of the main character in the film Ngeri-Ngeri Sedap by Bene Dion, analyze personality types based on literary psychology studies, and identify the role of the father in the film. The method used is descriptive qualitative with data collection techniques through film observation, listening techniques, and taking notes. The analysis was carried out in three stages, namely data reduction, data presentation, and drawing conclusions. The results of the study indicate that the main character in the film has various personalities, such as being easily angered, stubborn, patient, and careful in expressing opinions. Based on the analysis of literary psychology, the personality types found include gepasioner, phlegmatic, choleric, nerveuzen, and sentimental. In addition, this film depicts a father figure who plays a role as a decision maker, monitor, and protector for his family. These findings indicate that Ngeri-Ngeri Sedap not only presents family conflicts but also provides reflections on the psychological and social dynamics in parent-child relationships.